ANALISIS PERUBAHAN IKLIM BERBAGAI VARIABILITAS CURAH HUJAN DAN EMISI GAS METANA (CH4) DENGAN METODE GRID ANALYSIS AND DISPLAY SYSTEM (GrADS) DI KABUPATEN SEMARANG - Ismi Dian Kusumawardhani; Rahmat Gernowo (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
Global climate change as the implications of global warming caused by greenhouse gas increases from time to time. Methane (CH4) is a greenhouse gas that causes the greenhouse effect and has the effect of 20-30 times greater than carbon dioxide. The rate of CH4 emissions to the atmosphere is the fastest among other greenhouse gases.The research was conducted by analyzing climate change using the data of precipitation, air temperature, and methane emissions. Data of Ungaran - kabupaten Semarang precipitation obtained from Badan Meteorologi, Klimatologi dan Geofisika (BMKG) Climatological Station Semarang. Globally available data of precipitation and air temperature, that is downloaded from the website National Oceanic and Atmospheric Administration (NOAA). While the emission data of methane (CH4) is obtained from Badan Lingkungan Hidup (BLH) Central Java with data that covers an area of Central Java. To determine the existence of climate change in the research area of data analysis is carried precipitation and air temperature during the last 30 years. The method used is the method of Grid Analysis and Display System (GrADS) that can be used for processing and visualizing the earth science data.The results of this study, the increase in precipitation and air temperature every year in a period of 30 years in kabupaten Semarang. The average amount of precipitation every year is obtained by 1579.86 mm. Precipitation in Central Java region shown by the pattern of monsoon rainfall. The average maximum precipitation in January, while the minimum in August. The average air temperature increase annually by 0.014oC or 0.051% every year. Similarly, the amount of methane emissions (CH4) in all parts of human activity in the region of Central Java has increased every year. The average increase of CH4 emission obtained annually by 14.99 Gg or 1.36%. On average generated methane emissions from human activities annually by 1104.54 Gg.Keywords: Global warming, climate change, GrADS, precipitation, methane emissions (CH4)